2022
DOI: 10.1155/2022/9443407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IL20RB as a Novel Prognostic and Therapeutic Biomarker in Clear Cell Renal Cell Carcinoma

Abstract: Background. Clear cell renal cell carcinoma (ccRCC) is a type of life-threatening malignant tumor of the urinary system. IL20RB, interleukin 20 receptor subunit beta, is a cytokine receptor subunit coding gene and was initially found to play a vital role in human cancers, while its role in ccRCC still remains unclear. Methods. In this work, we explored the prognostic value and therapeutic potential of IL20RB in ccRCC mainly by online tools. Firstly, we used UALCAN and GEPIA to explore the expression profile an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…A previous study found that IL20RB (interleukin 20 receptor subunit beta) functioned in papillary renal cell carcinoma through the EMT pathway 27 . A recent study reported that upregulated IL20RB is confirmed as a novel prognostic and therapeutic biomarker in KIRC, which is consistent with our results 28 . It was also reported that downregulated DDC is significantly associated with poor survival and an immune‐suppressive TME in KIRC 29 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A previous study found that IL20RB (interleukin 20 receptor subunit beta) functioned in papillary renal cell carcinoma through the EMT pathway 27 . A recent study reported that upregulated IL20RB is confirmed as a novel prognostic and therapeutic biomarker in KIRC, which is consistent with our results 28 . It was also reported that downregulated DDC is significantly associated with poor survival and an immune‐suppressive TME in KIRC 29 .…”
Section: Discussionsupporting
confidence: 91%
“…27 A recent study reported that upregulated IL20RB is confirmed as a novel prognostic and therapeutic biomarker in KIRC, which is consistent with our results. 28 It was also reported that downregulated DDC is significantly associated with poor survival and an immune-suppressive TME in KIRC. 29 Another study confirmed that decreased TEK expression had a poor prognosis for patients with KIRC.…”
Section: Discussionmentioning
confidence: 95%
“…Many human malignancies exhibit dysregulated IL20RB expression, which is remarkably high in KIRC. Previous work has shown that IL20RB can be used as a prognostic biomarker for tracking KIRC treatment (Guo et al, 2022). Abnormal expression of IFI30 has also been found in many human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of IL10R2 contributes to colorectal carcinogenesis by IL22/STAT3 signaling (24). IL20RB has been proposed as a prognostic and therapeutic biomarker in clear cell renal cell carcinoma (25).…”
Section: Discussionmentioning
confidence: 99%